Notes on recollection and extended distribution of Rhynchotechum alternifolium C.B.Clarke (Gesneriaceae) in Eastern Himalaya, Bhutan - Odyuo, Nripemo; Roy, Dilip Kr. (International Journal of Environment, 2017)
Rhynchotechum alternifolium C.B.Clarke, a Gesneriaceae plant taxon earlier known from India and Myanmar, is reported here as an extended distribution to Bhutan. In India, earlier it was reported from Arunachal Pradesh, Assam, Manipur and Nagaland. The last observation of this taxon was in 1962 from Myanmar. During recent field exploration (2015), it is once again reported from Nagaland. Based on herbaria records, it is also recorded from Sikkim Himalaya. Brief taxonomic description along with photographic illustration and distribution map of the taxon is provided. Further investigation is required in the eastern Himalaya and North-eastern region of India to ascertain its present population status as well as IUCN status for conservation point of view. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-2, Mar-May 2017, Page: 1-8